Dynamics of the Financial Stability of Islamic Banking in Malaysia: Current Perspective Analysis - Isamail, Mohamad Zaim; Rosele, Muhammad Ikhlas; Md. Ariffin, Mohd Farhan; Jailani, Munawar Rizki; Ismail, Syaimak (Al-Risalah, 2020)
This article discusses the financial stability of Islamic banking in Malaysia by focusing on the analysis of current perspectives. In addition, it also discusses the references used to describe Islamic-based financial stability. To achieve this objective, this study would analyse the resources to ascertain the arguments on how such financial stability is viewed from an Islamic perspective. This study was conducted using a qualitative method through library research by searching for references from sources such as al-QurÊ¼an and its interpretation, al-Hadith of the Prophet Muhammad peace be upon him and also arguments by Islamic scholars. The results of this study showed that certain texts in al-QurÊ¼an and al-Hadith, as well as the views of scholars, acknowledge that financial stability has a strong foundation based on authentic sources. In the context of Islamic banking in Malaysia, various aspects need to be taken into account to ensure that these banking institutions continue to remain relevant in the domestic and international financial arena. In this regard, to ensure the stability and strength of Islamic banking institutions in Malaysia, these institutions need to fully adapt the banking model recommended by the shariÊ»ah, which would not only strengthen this industry but also make it capable of facing challenges and being resistant to financial crises and economic imbalances.